(untitled) (Nepalese Journal of Radiology, 2014)
We present a case of 61years old female, clinical manifestations of this entity, including left lumber continuous pain and discomfort with numbness at left gluteal region for 2 years. Pain had increase since one week with radicular pain in left leg. MRI study was performed with 3.0T unit (siemen) and revealed an oval shape mass behind the L3 vertebra, suggesting differential diagnosis of Neurilemoma or Ependymoma. The patient underwent surgical L3 laminectomy and total excision of the tumor. Pathological report confirmed diagnosis of Neurilemoma.# DOI: http://dx.doi.org/10.3126/njr.v4i1.11369 Nepalese Journal of Radiology, Vol.4(1) 2014: 47-51